Epitopes of Naturally Acquired and Vaccine‐Induced Anti‐Ebola Virus Glycoprotein Antibodies in Single Amino Acid Resolution. Issue 9 (8th June 2020) - Heidepriem, Jasmin; Krähling, Verena; Dahlke, Christine; Wolf, Timo; Klein, Florian; Addo, Marylyn M.; Becker, Stephan; Loeffler, Felix F.
Abstract: The Ebola virus (EBOV) can cause severe infections in humans, leading to a fatal outcome in a high percentage of cases. Neutralizing antibodies against the EBOV surface glycoprotein (GP) can prevent infections, demonstrating a straightforward way for an efficient vaccination strategy. Meanwhile, many different anti‐EBOV antibodies have been identified, whereas the exact binding epitopes are often unknown. Here, the analysis of serum samples from an EBOV vaccine trial with the recombinant vesicular stomatitis virus‐Zaire ebolavirus (rVSV‐ZEBOV) and an Ebola virus disease survivor, using high‐density peptide arrays, is presented. In this proof‐of‐principle study, distinct IgG and IgM antibodies binding to different epitopes of EBOV GP is detected: By mapping the whole GP as overlapping peptide fragments, new epitopes and confirmed epitopes from the literature are found. Furthermore, the highly selective binding epitope of a neutralizing monoclonal anti‐EBOV GP antibody could be validated. This shows that peptide arrays can be a valuable tool to study the humoral immune response to vaccines in patients and to support Ebola vaccine development. Abstract : The Ebola virus glycoprotein is displayed as 662 overlapping linear peptides in single amino acid resolution on microarrays. With these, IgG and IgM responses from Ebola vaccine recipients, an Ebola disease survivor, and a highly neutralizing monoclonal antibody are screened. Identified epitopes are compared with literature epitopes and show that peptide arrays are suitable to quickly evaluate serum antibody responses.